83.6k views
4 votes
Find the sum of the product (x-2) (2x+3) using any method

1 Answer

2 votes

Since both of the factors are binomials, FOIL Method may be used.

Product of the First terms: (x)(2x)= 2x²

Product of the Outer terms: (x)(3)= 3x

Product of the Inner terms: (-2)(2x)= -4x

Product of the Last terms: (-2)(3)= -6

Since the product of the outer and the inner terms are like terms, we may add the two products.


3x+(-4x)=-x

Thus, combining all terms in one expression would be as follows.


\begin{gathered} (x-2)(2x+3)=2x^2+3x-4x-6 \\ (x-2)(2x+3)=2x^2-x-6 \end{gathered}

User Srujan Reddy
by
5.2k points